Non-linear dose-response relationship between the visceral adiposity index and diabetes in adults with normoglycemia: a cohort study - Liang, Xiaomin; Xing, Zemao; Li, Ying; Gui, Shuiqing; Hu, Haofei (Frontiers in Endocrinology, 2024)
Objective Previous studies have identified a positive link between the visceral adiposity index (VAI) and diabetes in specific populations. Our investigation focused on examining this association in normoglycemic adults in Japan. Methods A cohort study of NAGALA (NAfld in the Gifu Area Longitudinal Analysis) was undertaken from 2004 to 2015 in Japan. The link between VAI and diabetes was evaluated using multivariate Cox proportional hazards regression and restricted cubic spline (RCS) regression models. Receiver operating characteristic (ROC) curve analysis was performed to assess the predictive value of the VAI for incident diabetes. Results Our study included 15,452 participants, with 8,418 men (54.48%) and 7,034 women (45.52%). The average age was 43.71 ± 8.90, and 373 participants (2.41%) developed diabetes. VAI was positively related to diabetes (HR=1.13, 95% CI 1.08-1.18). The inflection point of the non-linear relationship was observed at a VAI value of 4.67. For the VAI values up to 4.67, one unit increase in the VAI related to a 24% increase in new-onset diabetes (HR=1.24, 95% CI 1.12-1.37, p<0.0001). Subgroup analysis detected a more robust relationship in women (HR=1.40, 95% CI 1.14-1.70, p=0.0010). ROC analysis indicated that VAI, with an AUC of 0.7479 (95% CI: 0.7237-0.7720), had good predictive power. Conclusion Our cohort study validated the positive and non-linear relationship between the VAI and diabetes in normoglycemic adults in Japan. The relevance was more marked in women than in men. For those with a VAI below 4.67, a further reduction in the VAI could potentially lead to a significant decrease in diabetes risk.